Are (second generation) young immigrants active citizens?: Case of the Netherlands. Issue 2 (1st June 2017) - Skład, Marcin; Krzywosz-Rynkiewicz, Beata; Zalewska, Anna M.
The Netherlands is a country of diverse, often contradictory and dynamically changing views and policies with regard to civic integration of immigrants. In this context, studying how young Dutch immigrants express their citizenship may provide valuable insight. This research analyses how Dutch youth of immigrant and local origin differ in forms of expression of their citizenship, with a special distinction between immigrants of western and non-western origin. Results of an analysis of a convenience sample of 376 Dutch students aged 10–19 years revealed that immigrant status was related to significant differences between students on several dimensions of citizenship, in particular in its passive forms: national identity and patriotism. National identity was significantly higher among youth who were not from an immigrant origin, while with respect to patriotism both youth without an immigrant origin and those of western immigrant origin scored higher compared with children of immigrants with non-western roots. Children of immigrants from western countries scored higher than youth of non-western descent and native Dutch children on three dimensions of (semi-)active citizenship: intention to vote; action for change; and civic virtues. Study results confirmed the concern that young immigrants of non-western origin in particular struggle with identification with the host country. It did not confirm popular concerns about limited loyalty to the host country or lack of civic engagement among young (second-generation) immigrants. The results of the study should be generalized with caution due to the nature of the utilized sample.